Facilitating Spaces of Urban Agroecology: A Learning Framework for Community-University Partnerships - Nicklay, Jennifer A.; Cadieux, K. Valentine; Rogers, Mary A.; Jelinski, Nicolas A.; LaBine, Kat; Small, Gaston E. (Frontiers in Sustainable Food Systems, 2020)
At the local scale in Minneapolis/St. Paul (MSP), MN, urban farms, community gardens, and home gardens support diverse individual and community goals, including food access and sovereignty, recreation and outdoor activity, youth education, and racial, economic, and environmental justice. Collaborations between urban growers, policymakers, scholars, and communities that leverage urban farms and gardens as sites of ecological, social, and political transformation represent spaces of urban agroecology. Participatory research can play a vital role in urban agroecology by facilitating integration of science, movement, and practice, but frameworks to accomplish this are still emerging. This paper, therefore, proposes a “learning framework” for urban agroecology research that has emerged from our community-university partnership. We -- a group of growers, community partners, and researchers -- have worked with each other for five years through multiple projects that broadly focused on the socio-ecological drivers and impacts of urban farms and gardens in MSP. In fall 2019, we conducted our first formal evaluation of the participatory processes implemented in our current project with the objectives to 1) identify processes that facilitated or were barriers to authentic collaboration and 2) understand the role of relationships in the participatory processes. Qualitative surveys and interviews were developed and conducted with researchers, partners, and students. Analysis revealed that urban agroecology research provided a space for shared learning, which was facilitated through co-creation of research, embodied processes, and relationships with people, cohorts, and place. As part of our partnership agreements, we as researchers wrote this article -- in close consultation with partners -- to share this framework in the hopes that it will serve as a model for other research collaborations working within complex urban agroecological systems.